USING PRODUCT LIFE CYCLE COSTS IN ACCORDANCE WITH SUSTAINABILITY ACCOUNTING STANDARDS TO ACHIEVE CLEANER PRODUCTION-AN APPLIED STUDY IN THE NATIONAL COMPANY FOR CHEMICAL AND PLASTIC INDUSTRIES - Maytham Abbas Khudhair Al-Salmawi; Mohammed Alwan Rahima Al-Eqabi (Scholar Express Journals, 2025)
This research aims to apply the notion of product life cycle costs in agreement with sustainability accounting standards, in order to achieve cleaner production, reduce costs, and reduce environmental risks. The use of this technology, which classifies costs into costs that are harmful to the environment and others that are harmless according to the stages of production, will contribute to providing accurate Details on the environmental factors linked to industrial activities inside the factory, which helps to understand their environmental impacts and damages. The research problem is the continuous increase in product costs and environmental risks resulting from lack of adaptation to modern developments, as well as the growing gap between increasing material needs and shortage of natural resources. Therefore, promoting the concept of sustainability and product life cycle accounting towards cleaner production is crucial for global economic and social development.
Keywords: product life cycle; sustainability accounting standards; cleaner production